TuBaFrost: European virtual tumor tissue banking. - Riegman, P; Oomen, M; Dinjens, W; Oosterhuis, J; Lam, K; Spatz, A; Ratcliffe, C; Knox, K; Mager, R; Kerr, D; Pezzella, F; Van Damme, B; et al. (2006)
TuBaFrost is a consortium responsible for the task to create a virtual European human frozen tumor tissue bank, composed of high quality frozen tumor tissue collections with corresponding accurate diagnosis stored in European cancer centers and universities, searchable on the Internet, providing rules for access and use and a code of conduct to comply with the various legal and ethical regulations in European countries. Such infrastructure would enlarge tissue availability and accessibility in large amounts of specified or even rare tumor samples. Design of an infrastructure for European residual tissue banking with the described characteristics, clear focus points emerge that can be broken down in dedicated subjects: (1) standardization and quality assurance (QA) to avoid inter-institute quality variation; (2) law and ethics enabling exchange of tissue samples possible between institutes in the different European countries, where law and ethics are characterized by a strong variability; (3) rules for access, with sufficient incentives for collectors; (4) central database application containing innovations on search and selection procedures; (5) support when needed with histology images; and (6) Internet access to search and upload, with in addition a solid website giving proper information on the procedures, intentions and activities not only to the scientific community, but also to the general public. One consortium decision, part of the incentives for collectors, had major impact on the infrastructure; custodianship over the tissues as well as the tissues stay with the collector institute. Resulting in specimens that are not given to an organization, taking decisions on participation of requests, but instead the local collected tissues stay very easy to access by the collector and allows autonomous negotiation between collector and requestor on cooperation, coauthorship in publication or compensation in costs. Thereby, improving availability of large amounts of high quality samples of a highly specified or rare tumor types and contact opportunities for cooperation with other institutes.